Triple touch sperm immobilization vs. single touch sperm immobilization in ICSI - a randomised trial - Velaers An; Paternot Goedele; Debrock Sophie; D'Hooghe Thomas; Spiessens Carl (BMC, 2012)
Abstract Background Although different techniques for sperm immobilization have been described, their value has not been assessed in an adequately powered randomized study. The aim of this study was to compare two types of sperm immobilization methods prior to ICSI and to test the hypothesis that triple touch immobilization (TTIm) would lead to a higher (5% -65% up to 70%) fertilization rate (FR) than single touch immobilization (STIm). Methods A total of 3056 metaphase II (MII) oocytes, from 290 patients, were randomly assigned to the STIm group (n = 1528 oocytes; 145 cycles) or to the TTIm group (n = 1528 oocytes; 138 cycles). A total of 1478 oocytes (STIm group) and 1476 oocytes (TTIm group) were used in the statistical analysis. The primary outcome variable was FR. Secondary outcome variables included: number of good quality embryos (GQE) on day 2 and day 3, implantation rate (IR) and implantation with foetal heart beat rate (FHB). Statistical analysis was done using the Fisher Exact test with a significance level of 0.05. Results The results showed no differences in FR between both groups. The proportion of good quality embryos on day 3, was significantly higher in the STIm group (37.5%) compared to the TTIm group (31.8%; p = 0.02). Conclusions In this RCT, the hypothesis that the post-ICSI FR would be higher after TTIm than after STIm was not confirmed and the number of good quality embryos on day 3 was significantly lower in the TTIm group than in the STIm group. These data suggest that more 'aggressive' TTIm technique has no advantages compared to the STIm technique.